(untitled) (Journal of Economics and Sustainability, 2024)
Corporate social responsibility (CSR), a concept which existed for almost a century, is gaining traction in both commercial and academic spheres. Firms are experiencing greater pressures to realize more reasons to make more non-financial disclosures, especially on information related to their CSR initiatives. Even though some countries have implemented some forms of mandatory disclosure requirements, corporate executives continue to retain substantial autonomy in deciding the quality and extent of their corporate social responsibility disclosures (CSRDs). 128 articles published from 2006 to 2022 were found in the Scopus and Web of Science databases using a systematic literature review technique. This study offers a comprehensive mapping of the research works conducted, theoretical frameworks cited, and various determinants of CSRD. This study reveals that legitimacy theory, agency theory, and stakeholder theory are commonly cited in CSRD literature. Many country-level, firm-level, and individual-level determining factors affecting the quality and quantity of CSRD were discovered. This research made valuable contributions to the extant literature on CSR across multiple dimensions. Lastly, this study also identifies potential research avenues for academics to further the expanding body of knowledge in CSR.